Die DM ist tot! Es lebe der Euro!? Die 50jährige Geschichte der DM und die Perspektiven des Euro - Altvater, Elmar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The paper compares the German currency reform in 1948, the German monetary union in 1990, and the European currency union in 1999. Because of special national and international conditions the currency reform in 1948 was the starting point of West German economic prosperity. Under present, quite different economic conditions it seems not very likely, that this success story will occur again with the installation of the Euro.